Design of Web-Based Motor Vehicle Spare Parts Sales Application Using the Rapid Application Development (RAD) Method - Wirapraja, Alexander; Kardinata, Eunike Andriani (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2025)
The development of technology, especially in the industrial era 4.0 and the era of technological disruption accompanied by the increasing literacy of society in technology, has influenced the operations of a business company, especially in their marketing methods as the front line of a business process. Company X in Surabaya, which is engaged in the sale of motor vehicle spare parts, is one of the companies that is aware that the market continues to grow and they must follow these changes by designing a sales website to increase their revenue. This sales website was developed using the rapid application development (RAD) method because this method is suitable for developing software on a small to medium scale and has advantages in terms of efficiency of work time. The results obtained from the design of this sales information system software are a system that can help company X in managing spare part sales as a whole with features that include product catalogs, product transactions, multiple payments, shipping calculations, return menus, customer satisfaction ratings and sales reports per time period.